Bioactivities of methanol extracts from rhizophora apiculata blume and rhizophora mucronata lam. barks - Aqilah Nabihah, Anuar (Universiti Malaysia Sarawak (UNIMAS), 2015)
Natural product has been increasingly popular among the consumers, people starts to look for alternative from these natural products than continuing using the synthetic products especially for medicinal or domestic appliances. The objectives of this study were, first to determine the amount of extractives present in the bark of R. apiculata and R. mucronata using methanol as the solvent, and second was to determine the toxicity of the bark extracts against pathogenic microorganisms through series of bioassay tests at different concentration. For the study on the antifungal properties, bioassay was performed on Fusarium oxysporum and Aspergillus niger using agar dilution method while paper disc diffusion method was performed on Candida albicans. The minimal inhibition concentration for the tested fungi was 1 % for agar dilution method and for C. albicans, 0.01 % of the extracted crude. Screening on the antibacterial properties of the methanol extract, paper disc diffusion method was used on E. coli and S. aureus at different concentration. Among the two extracts, R. mucronata showed higher potential with antifungal and antibacterial than compared with bark extract from R. apiculata however after performing a two way ANOVA, it was revealed that there was no significant different on the antibacterial properties between the two studied species.